Graphene Plasmon Resonances for Electrically-Tunable Sub-Femtometer Dimensional Resolution - Zhiyong Wu; Lei Zhang; Min Zhang; Irene Ling Li; Hong Su; Huancheng Zhao; Shuangchen Ruan; Huawei Liang (Nanomaterials, 2020)
A coupled graphene structure (CGS) is proposed to obtain an electrically tunable sub-femtometer (sub-fm) dimensional resolution. According to analytical and numerical investigations, the CGS can support two branches of localized surface plasmon resonances (LSPRs), which park at the dielectric spacer between two pieces of graphene. The coupled efficiencies of the odd-order modes are even four orders of magnitude higher than that of the even-order modes. In particular, a sub-fm resolution for detecting the change in the spacer thickness can be reached using the lowest order LSPR mode. The LSPR wavelength and the dimensional differential resolution can be electrically-tuned from 9.5 to 33 μm and from 4.3 to 15 nm/pm, respectively, by modifying the chemical potential of the graphene via the gate voltage. Furthermore, by replacing the graphene ribbon (GR) at the top of the CGS with multiple GRs of different widths, a resonant frequency comb in the absorption spectrum with a tunable frequency interval is generated, which can be used to detect the changes in spacer thicknesses at different locations with sub-fm resolution.